2022
DOI: 10.3389/fnagi.2022.788296
|View full text |Cite
|
Sign up to set email alerts
|

Increased Susceptibility to Cerebral Microhemorrhages Is Associated With Imaging Signs of Microvascular Degeneration in the Retina in an Insulin-Like Growth Factor 1 Deficient Mouse Model of Accelerated Aging

Abstract: Age-related cerebrovascular defects contribute to vascular cognitive impairment and dementia (VCID) as well as other forms of dementia. There has been great interest in developing biomarkers and other tools for studying cerebrovascular disease using more easily accessible tissues outside the brain such as the retina. Decreased circulating insulin-like growth factor 1 (IGF-1) levels in aging are thought to contribute to the development of cerebrovascular impairment, a hypothesis that has been supported by the u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 88 publications
(123 reference statements)
0
12
0
Order By: Relevance
“…CBF is measured in the somatosensory cortex before and after whisker stimulation, and the increased CBF following stimulation is reflective of NVC response. Stimulation-induced increases in CBF were much lower in circulating IGF-1 deficient mice compared to controls ( 113 , 116 ). This impairment of NVC in IGF-1 deficiency supports a protective role for IGF-1 in vascular function.…”
Section: Role Of Gh/igf-1 In Regulation Of Cerebrovascular Functionmentioning
confidence: 77%
See 2 more Smart Citations
“…CBF is measured in the somatosensory cortex before and after whisker stimulation, and the increased CBF following stimulation is reflective of NVC response. Stimulation-induced increases in CBF were much lower in circulating IGF-1 deficient mice compared to controls ( 113 , 116 ). This impairment of NVC in IGF-1 deficiency supports a protective role for IGF-1 in vascular function.…”
Section: Role Of Gh/igf-1 In Regulation Of Cerebrovascular Functionmentioning
confidence: 77%
“…Older adults with low circulating IGF-1 levels have 39% higher risk of cardiovascular mortality ( 112 ). Animal models of circulating IGF-1 deficiency serve as models of accelerated aging ( 18 , 21 , 93 , 113 120 ), mimicking many age-related cerebrovascular pathologies.…”
Section: Regulation Of Aging Processes By the Gh/igf-1 Axismentioning
confidence: 99%
See 1 more Smart Citation
“…Increased oxidative stress and consequential increases in cellular DNA damage are important mechanisms of endothelial senescence. Considering the previously documented protective effects of IGF‐1 against oxidative stress and other cellular stressors, 13,14,16–18,47,73–81 we hypothesize that endothelial‐specific knockdown of IGF1R would impede these protective effects. Our results accord with emerging evidence that IGF‐1 may play a critical role in modulating cellular senescence in various age‐related diseases, such as atherosclerosis 70–72 .…”
Section: Discussionmentioning
confidence: 97%
“…Supporting our accelerated aging phenomenon hypothesis ( 2 ). Another study showed that IGF-1 deficient mice exhibited worsened microhemorrhages, suggesting that the pro-vascular and protective effects of circulating IGF-1 in the preservation of brain health and maintenance of cognitive function ( 47 ).…”
Section: Discussionmentioning
confidence: 99%